Aplikasi Realiti Terimbuh (AR) Jurulatih Gim: Aplikasi Realiti Terimbuh Jurulatih Gim - Zakaria, Nurzarinah; Md Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2021)
A workout application in mobile phone is one of the platforms that a gym trainer can use to share the knowledge regarding gym workouts. Users of the application, which are newcomers in the gym, can simply learn and develop their fitness and muscle strength without needing to pay a personal trainer. Workout application also can be used to make gym workout tutorials more accessible to newcomers because information regarding the workout is now only available at the user's fingertips. The Augmented Reality Gym Trainer (AR Trainer) application will provides a variety of workouts that appropriate for newcomers.